The Effect of Inclusive Education Training on Teachers’ Social and Personality Competencies - Irda Murni; Nurhastuti; Johandri Taufan; Ardisal; Teguh Wijaksana Isma (INCLUSIVE EDUCATION, 2023)
Inclusive education system is a new challenge for teachers in teaching and learning activity. Homogeneity in learning activity has always been there but inclusive education system brings a new setting where regular students and students with special needs learn in the same classroom. The issue emerges due to teachers’ lack of competencies in implementing inclusive education. For this reason, teachers need to be provided with training on inclusive education. This research aims to examine whether teachers’ competencies can be improved through inclusive education training, specifically for social and personality competencies. This research used associative method which aims to find the influence of training on teachers’ social and personality competencies. The samples selected for this research were 42 elementary school teachers in inclusive education. The technique of data analysis used was T-test. Findings showed that inclusive education training has improved teachers’ social competency, while it gives no influence on teachers’ personality competency.